Edukasi Petugas Puskesmas dan Hubungannya dengan Oral Hygiene Siswa Sekolah Dasar di Sinjai, Sulawesi Selatan - Abdullah, Nurwiyana; Asridiana; Nur Aida, Wanda; Supriatna, Agus; Arif, Anugrah (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2024)
The prevalence of dental and oral diseases in Indonesia is still high, especially at ages 6-12 years. The results of Indonesian Basic Health Research in 2018 showed that the prevalence of dental and oral problems was 57.6% and those who received services from dental medical personnel were 10.2% (Riskesda, 2018), to overcome this, community health center officers have the authority to serve . community in handling dental and oral health problems. This study aims to determine the relationship between visits and education by community health center officers and the oral hygiene of students at SDN 92 Panaikang, Kec. East Sinjai, Sinjai Regency. This research is quantitative research. The sample used was 78 elementary school students in grades 4, 5, 6. Data collection was carried out by directly examining students' dental and oral health and determining their OHI-S scores as well as administering questionnaires regarding students' knowledge regarding dental and oral hygiene issues. Data analysis used Chi-square to see the relationship between visits and education from community health center staff and students' oral hygiene. The research results showed that there was an increase in students' knowledge and OHI-S scores after visits and education by community health center officers. The chi-square test results show that there is a significant relationship between students' level of knowledge and their OHIS scores (P=0.000). It can be concluded that there is a relationship between visits and education by community health center officers and the oral hygiene of students at SDN 92 Panaikang, Kec. East Sinjai Sinjai Regency.